2013
DOI: 10.1097/inf.0b013e318290614f
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Outcomes and Predictors of Recovery in Childhood Encephalitis

Abstract: This study is unique in identification of race/ethnicity as an independent predictor of pediatric encephalitis outcomes. Additional variables may be useful ancillary tools in determining prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…9 Long hospital stay was also associated with poor prognosis in the present study and most likely reflects the severity of the disease. Other factors that reflect severity of disease, such as low Glasgow Coma Scale score on admission, 15,28,37 deep coma, 28 and ICU admission, 14 were previously found as poor prognostic factors in other studies (although not in the present study). Several authors have suggested that young age is associated with a poor long-term prognosis in children with encephalitis.…”
Section: Figurementioning
confidence: 37%
“…9 Long hospital stay was also associated with poor prognosis in the present study and most likely reflects the severity of the disease. Other factors that reflect severity of disease, such as low Glasgow Coma Scale score on admission, 15,28,37 deep coma, 28 and ICU admission, 14 were previously found as poor prognostic factors in other studies (although not in the present study). Several authors have suggested that young age is associated with a poor long-term prognosis in children with encephalitis.…”
Section: Figurementioning
confidence: 37%
“…In general, the predictors of poor outcomes were ICU admission and status epilepticus, as in previous studies. [40][41][42] In addition, we found diffusion restriction on MRI, a marker of cytotoxic injury, correlated with abnormal outcomes. The use of immunotherapy was not associated with better outcomes, but the patients receiving immune therapy had longer admissions, suggesting that these patients had a more complicated course.…”
Section: Discussionmentioning
confidence: 84%
“…Immunotherapy has only recently become established in the treatment of autoantibody-associated encephalitis (other than ADEM), 3 and prospective studies are needed to determine the benefit of immunotherapy in patients with encephalitis irrespective of whether an autoantibody is detected. The percentage of unknown encephalitis (28%) in this study is the lowest among substantial pediatric cohorts, [6][7][8]40,41 but it represents an important subgroup that is comparable in size to the prospective UK cohort in adults and children. 5 There were no distinguishing clinical or radiologic characteristics of the unknown subgroup, mainly because of the likely heterogenous etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of childhood infectious encephalitis has been reported in a number of large series from around the world [3,4,12,[23][24][25][26][27][28][29][30][31][32][33]. Recent publications have provided new information.…”
Section: Infectious Encephalitis Epidemiology Clinical Characteristicsmentioning
confidence: 98%
“…There are also toxic and metabolic syndromes that cause brain inflammation and can mimic infectious encephalitis [8], including Mild Encephalopathy with Reversible Splenial Lesions [9]. It is also well established that a high proportion of cases (between 30 and 70 % depending on the population studied) will not have an aetiology identified despite extensive investigation [1,4,5 •• ], although this proportion can be reduced with rigorous application of consensus guidelines [10,11].…”
Section: Introductionmentioning
confidence: 99%